Examining Digital Entrepreneurship: The Goal of Optimization of Transformation Path Normal Education in China - Zhao, Yang (Frontiers in Psychology, 2021)
The education system in China needs optimization with the erupted pandemic for effective outcomes. The path for normal education is upgrading itself with online learning, hence offering a challenge for entrepreneurship. The education sector needs to tackle these offered challenges better that optimizes and exploits the situations. The way teachers and students communicate and utilize their learning to materialize new ideas is very important for keeping pace. Therefore, this study is aimed to investigate the role of mentorship in digital entrepreneurship. The population for the study was the teachers of normal education in China. The sampling design used was convenient random sampling, and data were collected with a self-administered questionnaire on five points Likert scale. This study has used Smart PLS 3.3.3 (USA) for the data analysis through structural equation modeling. In the first stage, the instrument analyzed the measurement model, and in the second stage, the hypotheses were checked using the data collected. The findings of the study show that mentorship plays a very important role in knowledge sharing and innovation, which further leads to digital entrepreneurship. The study will open a new path in the education field to incorporate knowledge hidings and transformational entrepreneurship.